Bans of WHO Class I Pesticides in Bangladesh—suicide prevention without hampering agricultural output. (18th August 2017) - Chowdhury, Fazle Rabbi; Dewan, Gourab; Verma, Vasundhara R; Knipe, Duleeka W; Isha, Ishrat Tahsin; Faiz, M Abul; Gunnell, David J; Eddleston, Michael
Abstract: Background: Pesticide self-poisoning is a major problem in Bangladesh. Over the past 20-years, the Bangladesh government has introduced pesticide legislation and banned highly hazardous pesticides (HHPs) from agricultural use. We aimed to assess the impacts of pesticide bans on suicide and on agricultural production. Methods: We obtained data on unnatural deaths from the Statistics Division of Bangladesh Police, and used negative binomial regression to quantify changes in pesticide suicides and unnatural deaths following removal of WHO Class I toxicity HHPs from agriculture in 2000. We assessed contemporaneous trends in other risk factors, pesticide usage and agricultural production in Bangladesh from 1996 to 2014. Results: Mortality in hospital from pesticide poisoning fell after the 2000 ban: 15.1% vs 9.5%, relative reduction 37.1% [95% confidence interval (CI) 35.4 to 38.8%]. The pesticide poisoning suicide rate fell from 6.3/100 000 in 1996 to 2.2/100 000 in 2014, a 65.1% (52.0 to 76.7%) decline. There was a modest simultaneous increase in hanging suicides [20.0% (8.4 to 36.9%) increase] but the overall incidence of unnatural deaths fell from 14.0/100 000 to 10.5/100 000 [25.0% (18.1 to 33.0%) decline]. There were 35 071 (95% CI 25 959 to 45 666) fewer pesticide suicides in 2001 to 2014 compared with the number predicted based on trends between 1996 to 2000. This reduction in rate of pesticide suicides occurred despite increased pesticide use and no change in admissions for pesticide poisoning, with no apparent influence on agricultural output. Conclusions: Strengthening pesticide regulation and banning WHO Class I toxicity HHPs in Bangladesh were associated with major reductions in deaths and hospital mortality, without any apparent effect on agricultural output. Our data indicate that removing HHPs from agriculture can rapidly reduce suicides without imposing substantial agricultural costs.